Evaluating the Scope and Consequences of Substituting Party Qualities or Status in Administrative Disputes in Terms of the Principles Governing Administrative Procedural Law - Cihan Yüzbaşıoğlu (İstanbul Hukuk Mecmuası)
In administrative justice, the substitution of parties due to death or any other reason while a process is still pending has important consequences on how procedural acts will continue and which rules of procedural law will be applied. Due to changes in the qualities or status of a party to a case, courts sometimes end and other times suspend proceedings. Meanwhile, a court’s decision to continue or suspend for an extended time procedural acts despite a party substitution may have consequences regarding the rights or interests of the parties to the case and those of third parties. However, determining whether or not a change has occurred in parties’ qualities or status is a matter related to civil, property, and commercial law, which requires examining the issue with a multidisciplinary approach. In addition to the concept being directly related to private law, its application both at first instance and at appeal proceedings requires finding solutions for many different scenarios. Despite the complex nature of the matter, Article 26 of Türkiye’s Administrative ProcedureAct, which regulates the substitution of parties, is far from able to respond to the needs. Although attempts have been made to fill the gaps through jurisprudence, difficulty is had in accepting that judicial decisions are consistent. This situation causes results that are incompatible with the principles of administrative procedural law, such as administrative stability, procedural economy, equality of arms, and especially the right to access the court; it also leads to conflicts or struggles among these principles.